The Impact of Parental Consulting on Vocational Development: An Intervention with 9th grade students and their respective parents - Gonçalves, Carlos Manuel (2019)
Parents, as significant elements, are being mentioned by research as fundamental in the processes underlying the construction of their children's vocational paths or trajectories. Departing from this statement in literature, this research tries to understand the impact of a parental consultancy project – outlined and co-constructed form a project process methodology, sustained by a Constructional, Ecologic and Developmental approach – upon their children's vocational development process. The quantitative assessment of the results was performed at two times (pre-test and post-test) for the three groups. In what concerns the efficacy of the intervention, the quantitative results, confirmed by the qualitative ones recorded during the process, point towards a clear added-value of the interventions of parental consultancy projects for the promotion of their children's vocational development, as highlighted and indicated by the statistically significant differences found, in terms of vocational investment, between GEI and GEII. The results also point towards enormous advantages of interventions, which choose a project methodology in detriment of occasional interventions, pre-programmed and predominantly focusing on education/information, as confirmed by the statistically significant differences found between the two experimental groups and the control group.